Most postoperative reserved “normal” metatarsal stumps of diabetic foot osteomyelitis are infected but have healing potential - Xu, Jun; Chen, Weiling; He, Lu; Feng, Shuhong; Zhang, Jinghang; Chang, Bai (Frontiers in Endocrinology, 2023)
Background: Although the pathology and bacterial status of the "normal" bone stump after operation of diabetic foot osteomyelitis (DFO) are of great significance for the prognosis of foot wounds, there are only a few studies on this topic; hence, it is clinically relevant and urgent to study this topic.Methods: The data of fifty-seven inpatients with DFO from June 2021 to April 2022 were collected, all of whom had DFO in the forefoot and underwent conservative surgery. After the surgical removal of necrotic bone, bone biopsies were taken from the necrotic phalangeal bone and the reserved "normal" metatarsal stump. They were cultured, after which antibiotic susceptibility test and pathological screening was carried out. According to clinical judgment, inpatients' wounds were divided into metatarsal affected group and metatarsal unaffected group. We then compared and analyzed the pathological and bacterial characteristics of preserved "normal" bone stump and its effect on wound healing and prognosis.Results: The poor concordance rate between deep soft tissue culture and infected phalange culture was only 19.3%. The deep soft tissue (72.6%), infected phalange (70.7%), and metatarsal stump (71.4%) were mainly infected with gram-negative Bacillus. The proportion of Enterococcus spp. increased significantly in bone tissue. Acinetobacter baumannii had the highest drug resistance (88%, 22/25).There was no significant difference in several clinical characteristics and wound healing regardless of whether their metatarsal stumps were affected. Most reserved "normal" metatarsal stumps (84.2%, 48/57) were positive by pathological diagnosis and bacterial culture testing; only 15.7% (9/57) samples were truly sterile. Only 8.3% (4/48) of the former patients healed within 6 months; whereas, This is a provisional file, not the final typeset article all the latter (9/9)patients samples healed within 6 months. However, the majority (89.6%, 43/48) could heal. There was no difference in operations, skin grafting, negative pressure wound therapy, and mortality between the two groups.The most reserved "normal" metatarsal stumps have been invaded by bacteria. However, the majority stumps can be preserved and the wound eventually be healed according to the pathological and bacterial culture results.